Postgraduates’ perceptions in completion of their study - Teoh, Sian Hoon; Narayanan, Geethanjali; Raja Mohamad, Raja Normi; Sidhu, Gurnam Kaur (UiTM Cawangan Johor, 2021)
Today's international business scholars treat language as an issue at the heart of their subject area (Mughan 2015), as English language's irreplaceable position as means of communication is considered essential for international businesses. Nevertheless, one of the main concerns of educational specialists is the relevance of their programmes to the graduates' success in today's highly competitive labour market. With that, a needs analysis study was sought to explore the English language needs of undergraduate accounting students at Universiti Putra Malaysia. A survey method was employed to 20 undergraduate accounting students for the purpose of this study. The data collected from the sun1ey were analysed quantitatively using SPSS 22 programme. As the findings of this study pointed out, the participants prefer to be taught more in listening, speaking and writing skills as the needs for their study and fi,1ture career. Henceforth, a highly structured ESP course for accounting students with integration of language skills, subject or field-special skills, derived from their needs should be designed.